Is intrauterine growth retardation with normal umbilical artery blood flow a benign condition?. Issue 6731 (21st April 1990) - Burke, G; Stuart, B; Crowley, P; Scanaill, S N; Drumm, J
Abstract : OBJECTIVE–To determine whether intrauterine growth retardation associated with normal umbilical artery blood flow is a benign condition. DESIGN–A prospective comparative study of growth retarded fetuses with normal and abnormal umbilical artery blood flow. SETTING–The fetal assessment clinic of a large maternity hospital in Ireland. PATIENTS–179 Women with singleton pregnancies in which the fetal abdominal circumference, measured by ultrasonography, was below the fifth centile for gestation. MAIN OUTCOME MEASURES–Perinatal deaths, fetal distress requiring caesarean section, preterm delivery, cerebral irritation. RESULTS–Of 124 fetuses with normal flow, all physically normal fetuses survived but one baby had cerebral irritation; there were six preterm deliveries and four caesarean sections for fetal distress. Among 55 women with abnormal flow there were two midtrimester abortions, three perinatal deaths, and one case of cerebral irritation in physically normal fetuses. CONCLUSIONS–Intrauterine growth retardation associated with normal umbilical blood flow is a different entity from that associated with abnormal flow, normal flow being largely benign and abnormal flow carrying a serious risk of adverse outcome.